Kinerja Pelayanan Penerbitan Kartu Tanda Penduduk Elektronik (Ktp-El) Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Karo - Situmorang, Ririn Lestari; Wulandari, Novita; Lubis, Yurial Arief (Universitas Medan Area, 2024)
This research has a background with the occurrence of cases that are currently emerging, namely the performance of services for issuing electronic identity cards (KTP-El) at the Karo district population and civil registration service. The purpose of this study was to find out and describe the performance of the publishing service (KTP-EL) in the Karo district population and civil registration service. This study uses a qualitative method that is descriptive using the Sadarmayanti Theory. Observation data collection techniques, documentation, and interviews. The results of this study show how the performance of the service for issuing electronic identity cards (KTP-EL). And obstacles in issuing electronic identity cards (KTP-EL) to the Karo district population and civil registration service. From the results of research on the service of issuing electronic identity cards (KTP-EL) at the Karo district population and civil registration service by directing all people who take care of electronic identity cards (KTP-EL) to take queue numbers, and provide seats for people who are queuing waiting for recording (KTP-EL). Obstacles encountered in issuing electronic identity cards (KTP-EL) at the Karo Regency population and civil registration service. It often happens that the network is unstable so the process of printing and recording electronic identity cards is hampered.